Silicon increased the growth, productivity, and nutraceutical quality of tomato (Solanum lycopersicum L.) - Juan J. REYES-PÉREZ; Hilda C. TIPÁN-TORRES; Luis T. LLERENA-RAMOS; Luis G. HERNANDEZ-MONTIEL; Tomas RIVAS-GARCIA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
Tomato (Solanum lycopersicum L.) is considered one of the most important horticultural crops worldwide due to its nutritional and organoleptic properties. Instead of chemical fertilizers, recent research has shown in several plant species the importance of silicon fertilization. Hence, the present investigation aims to evaluate the effect of three different doses (low, medium, and high dose) of silicon on the growth (stem length and diameter, root length diameter, and stem, leaf and root biomass), productivity (polar and equatorial fruit diameter, number of fruits per bunch and plant, and yield), and nutraceutical quality (total soluble solids, titratable acids, and vitamin C) parameters of tomato. The Si treatment affected the evaluated parameters in a dose dependent way in almost all the parameters evaluated. Despite the tomato is classified as a non-Si accumulator, it has a significant response to Si treatment at a low dose of 0.15 g plant-1, medium dose of 0.25 g plant-1, and high dose of 0.35 g plant-1 after 120 d of transplantation in terms of plant growth, yield, and quality parameters. The effectiveness of Si nutrition is dependent on factors such as element source, plant species, and cultivar, and even, the absorption and bioaccumulation capacity of this element could be different between varieties.